Zabezpieczenie majątkowe na poczet kary grzywny - Antkowiak, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The present study discusses the issue of security on property institution with reference to a fine.The article presents the essence of the matter and the main goal of security on property. It points out the objective scope of the institution, ways of enforcement as well as legal regulations concerning the cancellation of security on property.The study also presents the types of and ways of implementing security on property. The attention is also paid to the importance of the discussed institution in the process of fine proceedings.
Keywords: grzywna; zażalenie; zabezpieczenie majątkowe; odpowiedzialność karna; postępowanie egzekucyjne